Analisis Manajemen Ruas Di Simpang Empat Pasar Sidoharjo Lamongan Menggunakan Algoritma Genetika - Yusnia Megasari; Mohammad Syaiful Pradana (UJMC (Unisda Journal of Mathematics and Computer Science), 2023)
A common problem in the traffic system is the inaccuracy of traffic lights on road conditions, often problems with these traffic lights cause traffic jams on roads, specifically at the intersection of four in Sidoharjomarkets, Lamongan district. In the section at the intersection of four Sidoharjo markets, the green light flashes in 3 phases, there are north, south, and east – westwhich are together, meaning that there are incompatible currents, namely two or more currents that are allowed to run together, potentially resulting in crowds. especially busy hours at the Sidoharjo market. Therefore, it takes traffic management to manage these problems. The use of Genetic Algorithm is used in this problem to find predictions for optimizing the cycle time phase of traffic lights. The results obtained are optimal for vehicle density of 30SSM/minute and red light delay time of 0.82 minutes